PENERAPAN PEMBELAJARAN TEMATIK POLUSI CAHAYA UNTUK MENINGKATKAN HASIL BELAJAR DAN PENANAMAN KARAKTER SISWA SMP - Fauziah, Hayyah (2013)
Pembelajaran IPA terpadu di SMP merupakan tuntutan kurikulum 2013 dan NSTA (National Science Teachers Association). Namun, di lapangan pembelajaran terpadu masih belum diimplementasikan secara optimal. Penelitian ini merancang dan mengimplementasikan pembelajaran IPA terpadu model webbed dengan tema polusi cahaya sebagai salah satu alternatif pembelajaran tematik integratif. Penelitian ini mengungkap hasil belajar siswa berdasarkan new taxonomy of science education yang terdiri dari lima domain yaitu domain knowing & understanding, science process skill, creativity, attitudinal dan connecting & applying. Metode penelitian ini yaitu mixed methods dengan desain penelitian concurrent embedded. Subjek penelitian yaitu salah satu kelas VIII SMP Negeri di Bandung berjumlah 27 siswa. Instrumen yang digunakan terdiri dari 28 soal tes, lembar observasi, serta tes dilema moral. Penerapan pembelajaran tematik ini menggunakan model pembelajaran Susan Loucks-Horsley (SLH). Berdasarkan hasil yang diperoleh, pembelajaran tematik mampu meningkatkan hasil belajar serta menanamkan karakter positif siswa pada tema polusi cahaya. Perolehan hasil belajar tersebut yaitu; rata-rata gain ternormalisasi domain knowledge sebesar 0,22 kategori rendah; prosentase domain science process skill sebesar 78,26% kategori baik; prosentase rata-rata domain creativity sebesar 72,91% kategori baik, rata-rata prosentase domain connecting sebesar 71,29% dan nilai prosentase rata-rata domain attitudinal lebih dari 75% pada aspek moral knowing, dan moral feeling. Kata Kunci : model tematik, new taxonomy of science education. Integrated learning is one of the 2013 development curricula persuit. Meanwhile, NSTA has recommended that science teachers in the elementary and intermediate schools should have interdicipliner preferences in science. Based on the preface research at one of the junior high school in Bandung, integrated learning still not applicated. Therefore this study applying integrated learning with webbed model in light pollution theme. It aimed to describe the students achievement based on new taxonomy of science education. Susan Loucks-Horsley (SLH) learning model was used for this implementation which consist of four phases there are invited, explore and discover, purpose explanation and solutions, and the last phase is taking action. This study using mixed methods with concurrent embedded design. The subject is second grade in junior high school in Bandung, Class 8A consist of 27 students. The Instrument that used are 28 questions with multiple choise related light pollution theme for measuring knowing and connecting domain, observation papers for measuring science process skill and creativity domain, and test of moral dilemma for measuring attitudinal domain. The data results based on new taxonomy of science education are; the average normalized gain of knowing and understanding domain reached 0,22 include low category, the average percentage of science process skill domain reached 78,26% with good category, the average percentage of creativity domain reached 72,91% with good category, the average percentage of attitudinal domain is over 75% in moral knowing and moral feeling, and the average percentage of connecting domain reached 71,29%. Based on this results showed that integrated learning with webbed model is able to increasing students achievement and invest positive characters on light pollution theme learning. Keywords: Susan Loucks-Horsley (SLH) learning model, new taxonomy of science education